2004
DOI: 10.1038/sj.eye.6701541
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of deep sclerectomy with implantation of chromic suture material as a collagen implant: medium-term results

Abstract: Aims A pilot study of the safety and efficacy of deep sclerectomy with a chromic suture implant (DSCI) for open angle glaucoma. Methods This prospective trial involved 23 eyes of 16 consecutive patients with uncontrolled open angle glaucoma. The DSCI procedure involved radial suturing of a 2 mm piece of 1/0 chromic suture as an implant. Intraocular pressure (IOP) measurements and eye examinations were performed preoperatively and regularly postoperatively for up to 66 months. Results The mean follow-up period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…25 The rate of postoperative 5-fluorouracil (5-FU) injection ranged between 4.6% and 43.6%. 20,21,23,24 In reports of DS with implant, the rate of goniopuncture ranged between 5.5% and 81%, 28,29,31,[33][34][35][37][38][39] with up to 45% (9 mm Hg) reduction in IOP, 34 and the rate of postoperative 5-FU injection ranged between 7% and 56%. 34,35,[37][38][39] The rate of goniopuncture after DS with antimetabolite could be as high as 46.9%, 37 and the rate of postoperative 5-FU injection as high as 28.9% (Table 2).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…25 The rate of postoperative 5-fluorouracil (5-FU) injection ranged between 4.6% and 43.6%. 20,21,23,24 In reports of DS with implant, the rate of goniopuncture ranged between 5.5% and 81%, 28,29,31,[33][34][35][37][38][39] with up to 45% (9 mm Hg) reduction in IOP, 34 and the rate of postoperative 5-FU injection ranged between 7% and 56%. 34,35,[37][38][39] The rate of goniopuncture after DS with antimetabolite could be as high as 46.9%, 37 and the rate of postoperative 5-FU injection as high as 28.9% (Table 2).…”
Section: Resultsmentioning
confidence: 95%
“…10, The percentage of cases achieving at least 21 mm Hg was 48.6% after primary DS (DS without any implant or antimetabolite), 10,[19][20][21][22][23][24][25] 68.7% after DS with implant, [26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 67.1% after DS with antimetabolite (with/ without implant) (Table 1). 21,[36][37][38] With lower set IOP targets, success ranged between 35% and 86% (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahan et al [8] described migration of an unsutured T-flux implant (nonabsorbable) in NPDS to the anterior chamber (A/C); the implant was removed without sequelae. Wevill et al [9] reported migration of chromic suture material used as an implant in NPDS to the anterior chamber after a blunt trauma to the eye. The implant was removed because of corneal edema and the anterior chamber reaction induced by its presence.…”
Section: Discussionmentioning
confidence: 98%
“…The requirements for any material used for ophthalmologic implants are in general sense the same; the material must be biocompatible, biostable and should have the microstructure suitable for fluid transport [4,5]. Such implants are to date made of natural polymers, e.g.…”
Section: Introductionmentioning
confidence: 99%